The Effectiveness of Career Counseling Services and Career Future Anxiety and their Relationship among High School Students in Jordan - Ahmad Al- Shraifin; Manar Bani Mustafa; Rami Tushtoosh (Sultan Qaboos University, 2014)
The study aimed to investigate the relationship between the effectiveness of career counseling services and career future anxiety among a sample of high school students in Jordan. The study sample consisted of 957 students selected randomly from the Directorate of Irbid. The study took place in the second semester of 2011/2012. The results indicated that the effectiveness of career counseling services perceived by the students was moderate, and the level of future career anxiety of the students was high. The correlation coefficients between the two scales were weak. There were statistically significant differences in the level of career counseling services in inviting experts and specialists due to gender in favor of males. Also, there were statistically significant differences attributable to the level of achievement in favor of high achievers. Also, the results revealed significant difference in the group and individual counseling sessions attributable to grade level in favor of grade 10. However, there was no significant difference in future anxiety attributable to any of the independent variables.